The Handwork subject in Waldorf Education: meanings through visual narratives - Selzler, Heloisa Sbrissia (2025)
This study explores the role of manual labor within the pedagogical context, focusing on children's engagement with the Handwork subject in Waldorf Education. Developed by Rudolf Steiner, this educational approach seeks to understand human beings holistically, emphasizing artistic and experiential learning. Within this framework, manual labor holds a significant place in the curriculum, regarded as an activity that nurtures human feeling and promotes harmony in the child, while also being closely connected to cognitive development. The research aimed to investigate the meanings and relationships that children construct through their experiences with manual labor as a curricular activity in Elementary School, specifically in a fifth-grade class of 17 students. An ethnographic approach was adopted, grounded in the principles of the Sociology of Childhood and the conception of children’s socialization as an interactive process (Corsaro, 2011). Data collection instruments included a field notebook and photography, the latter enabling the development of a visual ethnography. In addition to documenting the group through photographs, the study employed visual narratives—constructed through analytical frameworks proposed by Coutinho and Vieira (2019), Vieira and Coutinho (2019), and Coutinho (2010, 2016a, 2016b)—to express the children’s lived experiences with manual labor.